Are we better at judging traits we share with targets? : rater personality, trait accessibility and judgement accuracy - Gierdien, Zubeida (Department of Psychology, 2015)
Researchers and practitioners in the personnel selection and assessment field are interested in understanding the characteristics of a good rater. However, few studies have so far examined raters’ personality traits and trait accessibility as predictors of accuracy. The present study investigated the relationship between these individual difference constructs and judgement accuracy for specific traits. Respondents from a field sample (N = 223) of managers and staff employed in financial services completed the survey questionnaire and rated the personalities of five hypothetical interview applicants depicted in vignettes. Our results showed that raters’ personality traits and judgement accuracy for corresponding target traits were unrelated. In other words, raters were not more accurate at judging traits they shared with targets. However, we found that certain personality traits such as agreeableness and openness to experience were related to trait accessibility for the same trait-raters high on these traits also tended to perceive others in terms of them. In addition, accessibility for certain traits such as extroversion and openness to experience predicted judgement accuracy for the same traits. Therefore, these findings enrich our understanding of rater individual differences that may affect judgement accuracy.